Implementasi Media Audio Visual untuk Meningkatkan Critical Thinking Siswa Menggunakan Strategi Point Counterpoint - Ahmad Muhibbin; Ginda Tia Monica; Patmisari Patmisari; Achmad Muthali'in (ASANKA: Journal of Social Science And Education, 2021)
This study aims to describe the implementation, effectiveness, constraints, and solutions for the implementation of audio-visual media using the point-counterpoint strategy in class XI TKJ A SMK Adi Sumarmo Colomadu in the 2020/2021 school year. This study used a mixed-methods approach with a sequential exploratory design. Samples were taken using purposive sampling with a total of 28 students. Qualitative data collection techniques were interviews, observations, documentation, while quantitative data were analyzed using the Paired Sample T-Test hypothesis test. Test the validity of the data using triangulation of sources and techniques. The validity test using Correlation Product Moment with a significant level of 5% obtained a price of 0.444 and reliability using KR 20 with a result of 0.653. The qualitative analysis uses flow model analysis, while the quantitative analysis uses descriptive statistics. The results of this study are the implementation of audio-visual media to improve students' critical thinking using a point-counterpoint strategy by providing material through WhatsApp Group in the form of video. The effectiveness of the implementation of audio-visual media using the point-counterpoint strategy can be seen from the average results of the pretest 54.5 and posttest 81.6, with a total of 20 questions greater than T table (15,144 > 1,700). In this study, there were obstacles such as time constraints related to the implementation of the research. An alternative solution to overcome these obstacles is that researchers arrive earlier than the research schedule and must manage time well.